Optimization of Terpenoid Extraction from Bay (Syzygium polyanthum) Leaves using Ethanol as a Solvent by an Ultrasonic Wave Technology - Kusumaningrum, Maharani; Prasetiawan, Haniif; Setiyorini, Nurul; Dewanti, Astiara Anis; Rengga, Wara Dyah Pita (International Journal of Research Innovation and Entrepreneurship, 2020)
Bay is one of the medicinal plants. Bay leaves have been used in the pharmaceutical and food industry as an antimicrobial. The chemical compounds in the leaves that served as an antimicrobial were terpenoids. This study aims to determine the optimum extraction conditions of bay leaves using a response surface methodology (RSM). Ten grams of dried and mashed bay leaves was extracted for 60 minutes using ethanol as a solvent. The extraction was conducted at various temperatures (60, 70, 80 oC) and various ratios of the starting material to solvent (1: 8, 1:10, 1:12 g/g) for 60 min. The optimum extraction condition based on the RSM results was achieved at 70 Â°C with a ratio of the starting material to solvent of 1:12 g/g resulting in the extract yield of 9.69%. The results of the GC-MS analysis on the obtained extracts showed that 33% of terpenoids was obtained from the extraction at the optimum condition.